Fractal geometry: A consolidated tool for imagination - TÉLLEZ-MEDINA, Dario Iker (Vitae, 2013)
Since the very first attempts performed by the human brain for acquiring information about the surrounding world, priority is usually given to the information received by visual channels, i.e. by the eyes. It is interesting the proportion of human cerebral cortex destined for processing the stimuli captured by the photo-sensors contained in the retina, ranging 55%. According to several authors (1-4), the human learning process involves the association of each stimulus received by the different transduction assemblies composing the five senses to an image or, even, to a specific intricate memory. This has derived in formulating research works about how the brain develops the processes of creation and imagination. Therefore, the complexity of the well-known capacity of children for drawing in the mind (or in a piece of paper) a picture of an imaginary creature, and defining how it smells, hears, tastes, and touches, is astonishing. Having fun making an imaginary creature does not necessarily imply an easy task for the human brain, especially if the thinker of such an imaginary creature goes deeper into deciding if the creature becomes an opponent or a friend. In turn, the learning process may result affected when the visual channels do not work properly. Some studies have shown that lack of visual experience delays the physiological development of cognitive, social and linguistic skills in blind children. Although this might signify a serious disadvantage for an adequate brain development, there exist reports indicating that cerebral processing of shapes, spatial perception and imagery occurs in the same way and in the same highly-specialised visual areas, despite the sensory channels through which the information is acquired, in both blind and non-blind individuals. Furthermore, it is possible to mention many examples of blind persons noticing some aspects that the non-blind ones do not recognise.